Forgiveness dan Psychological well-being Santriwati dalam Menghadapi Budaya Senioritas: Studi Kasus di Pondok Pesantren - Suseno, Indah Khomaria; Khusumadewi, Ari (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study explores how forgiveness is interpreted by female students who experience seniority practices in an Islamic boarding school and how this process relates to aspects of psychological well-being. Previous studies have widely examined forgiveness and psychological well-being; however, limited research explains how forgiveness functions as a coping mechanism for students dealing with seniority dynamics within boarding school environments. Methods – This research employed a qualitative descriptive case study design. Data were collected through in-depth semi-structured interviews, observations, and documentation involving three female students of Madrasah Tsanawiyah (grades VII–IX) who had lived in the Islamic boarding school for at least six months and had experiences related to seniority interactions. Data analysis followed the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Credibility of the findings was strengthened through source triangulation involving caregivers and peers. Findings – The findings indicate that seniority experiences initially generated emotional responses such as fear, discomfort, and avoidance among participants. Findings suggest that participants interpreted forgiveness as a coping mechanism that helped them reinterpret seniority experiences and maintain aspects of psychological well-being Ryff, particularly self-acceptance, positive relations with others, and emotional regulation.Research Implications – This study provides insight into how forgiveness may function as a coping response in dealing with seniority dynamics in boarding school settings.